2019
DOI: 10.1177/0022034519849557
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between Income and Oral Health: A Critical Review

Abstract: In this critical review, we summarized the evidence on associations between individual/household income and oral health, between income inequality and oral health, and income-related inequalities in oral health. Meta-analyses of mainly cross-sectional studies confirm that low individual/household income is associated with oral cancer (odds ratio, 2.41; 95% confidence interval [CI], 1.59–3.65), dental caries prevalence (prevalence ratio, 1.29; 95% CI, 1.18–1.41), any caries experience (odds ratio, 1.40; 95% CI,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
109
3
14

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 133 publications
(136 citation statements)
references
References 77 publications
10
109
3
14
Order By: Relevance
“…The high prevalence of "fair"/"poor" perceived oral health and low utilization of services among the adult Medicaid expansion population in Kentucky found in this study is consistent with previous studies showing worse oral health outcomes and lower healthcare utilization among low-income individuals (8,22). While beneficiaries have had access to dental benefits since the 2014 expansion, perceived poor health likely reflects chronically poor oral health, which often requires uncovered treatments (i.e., root canals, crowns, and dentures) to replace teeth and recover form and function (23,24).…”
Section: Discussionsupporting
confidence: 91%
“…The high prevalence of "fair"/"poor" perceived oral health and low utilization of services among the adult Medicaid expansion population in Kentucky found in this study is consistent with previous studies showing worse oral health outcomes and lower healthcare utilization among low-income individuals (8,22). While beneficiaries have had access to dental benefits since the 2014 expansion, perceived poor health likely reflects chronically poor oral health, which often requires uncovered treatments (i.e., root canals, crowns, and dentures) to replace teeth and recover form and function (23,24).…”
Section: Discussionsupporting
confidence: 91%
“…Thereafter, a PubMed search using “intersectionality and oral health” and “intersectionality and dentistry” as keywords on the 30th January 2020 produced only six articles. These six articles included a critical review of income and oral health, which called for an intersectionality approach in its conclusion 33 . A further two papers mentioned intersectionality only in the discussion sections 34,35 .…”
Section: What Do We Know About the Application Of Intersectionality Imentioning
confidence: 99%
“…In addition, a recent meta-analysis confirmed that low individual/ household income was associated with several adverse oral health outcomes. 30 Thus, the current findings suggested that the socioeconomic condition is still a determining factor in the daily life of an individual, often more than esthetics is.…”
Section: Discussionmentioning
confidence: 62%